Cover Image. Issue 4 (9th March 2020) - You, Jiaqi; Mallery, Kevin; Mashek, Douglas G.; Sanders, Mark; Hong, Jiarong; Hondzo, Miki
Abstract : The cover image is based on the Original Article Microalgal swimming signatures and neutral lipids production across growth phases by Jiaqi You, Kevin Mallery, Mark Sanders et al., https://doi.org/10.1002/bit.27271 .